Faktor-Faktor Yang Mempengaruhi Current Ratio, Debt Equity Ratio, Debt Asset Ratio, dan Perputaran Modal Kerja Terhadap Return On Asset - Wafiyyah Septiwidya; Vina Ramadhianti; Juwainah Juwainah; Avriliani Dwi Septiana; Tri Yulaeli (Pusat Riset dan Inovasi Nasional, 2023)
Previous research or relevant research is very important in a research or scientific article. Previous research serves to strengthen the theory and phenomenon of interrelationships or influences return on assets. This article reviews the factors that influence the current ratio, debt equity ratio, and debt asset ratio an introductory literature study on Financial Management. This research aims to analyze the factors that influence the disclosure of Return on Assets namely: current ratio, debt equity ratio, debt-asset ratio, and working capital turnover. Sample selected by using purposive sampling method and samples that meet the criteria. Study This study uses the classical assumption test, model feasibility test, multiple regression analysis and statistical tests. These results indicate that the variable current ratio and debt equity ratio have an effect on return on assets, while the debt-asset ratio and working capital turnover variables are not shows the effect on the return on assets.